Produksi Konten Video Promosi Kreatif Pada Podcast Osari - Asroel Ramadhan; Dimas Umbroro (INDO PUBLISHING, 2026)
The rapid advancement of information technology has shifted the paradigm of media consumption from conventional platforms to dynamic audiovisual-based digital media. This study aims to analyze and describe in depth the production process of creative promotional video content for the Osari Podcast within the University of Bina Darma environment. The methodology employed is descriptive qualitative with an Action Research approach through an Independent Project practice. Data were collected through participatory observation, field documentation, and practical implementation during the production stages. The results indicate that the effectiveness of promotional content significantly depends on the harmonious integration between a structured pre-production stage, technical mastery during the production stage, and editing innovation in the post-production stage. The application of visual elements such as motion graphics, precise cinematography techniques, and